The Practice of Science and Religion Integration: Students’ Perspective on Muhammadiyah Pesantren - Naufal Ahmad Rijalul Alam; Fajar Rachmadhani (At-Ta'dib, 2021)
Islamic educational institutions in Indonesia have an important role in implementing science either from Islam, or the West with the breadth of knowledge. This study seeks to reveal the practice of Islamic education that integrates science and religious knowledge together. By taking the subject of students at Pondok Shabran, Surakarta, this qualitative research captures the extent to which the application of the integration of Islamic and Western knowledge is able to strengthen the understanding of students so that they get a portion that suits their needs. The result of the study shows, first, that the integration of knowledge through classroom learning has implications for improving the thinking skills of students. Second, the assignment given by the teacher gives students the freedom to read various kinds of Western literature that strengthens Islamic arguments.